2018
DOI: 10.1007/s13202-018-0550-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of testing conditions on the performance of lost circulation materials: understandable sealing mechanism

Abstract: Lost circulation materials (LCMs) are added to drilling fluids to mitigate lost circulation (LOC) problems. Designing the fluid requires a good understanding of sealing mechanisms and all the parameters affecting the sealing performance. Laboratory testing apparatus is the key concept for LCM evaluation ensuring successful treatment. The high-pressure test cell containing fracture discs is an effective tool among the broadly designed apparatus. A variety of formulations has been developed from the LCM physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…HDFS is responsible for storing the original data of power supply and the files processed by Map Reduce at the analysis layer. For the analysis layer, with the passage of time, the rapid development of the state grid, and the demand for data fusion of various networks and provincial companies, data storage capacity cannot be borne by a single file system, so a distributed file system with high expansion and high availability must be adopted for storage [18,19]. HDFS arises at a historic moment in the face of the need for mass data storage.…”
Section: Data Storage Layer Designmentioning
confidence: 99%
“…HDFS is responsible for storing the original data of power supply and the files processed by Map Reduce at the analysis layer. For the analysis layer, with the passage of time, the rapid development of the state grid, and the demand for data fusion of various networks and provincial companies, data storage capacity cannot be borne by a single file system, so a distributed file system with high expansion and high availability must be adopted for storage [18,19]. HDFS arises at a historic moment in the face of the need for mass data storage.…”
Section: Data Storage Layer Designmentioning
confidence: 99%
“…Jeennakorn et al have also described that the sealing mechanism of pores is mainly driven by particle size (coarse medium and fine), shape (irregular, elongated, and their blend), and amount (40, 50, and 105 ppb) of BM. 45 The larger size particles first enter the pores and reduce the pore throat significantly, thus bridging the pore at first attempt. This bridging is further followed by the deposition of medium sized particles to further fill the pores and reduces the FL (i.e., packing).…”
Section: Resultsmentioning
confidence: 99%
“…The primary method for testing the clogging effectiveness of lost circulation material is through the use of fracture or slot tests to evaluate LCM bridging in a drilling fluid passing through a fracture [11,23]. Our first test used a modified version of the API standard bridging materials tester.…”
Section: Single Fracture Testsmentioning
confidence: 99%
“…This method is ideal under the assumption that LC primarily occurs through pre-existing or drilling-induced fractures. However, research has shown that the specifics of the fracture test setup can drastically affect LCM performance results, and so results depend highly on the chosen conditions [23]. An additional issue with using fracture or slot tests for LCM experiments is that loss zones in geothermal drilling can include fault/shear zones, porous formations, and vugs or cavernous zones [1].…”
Section: Introductionmentioning
confidence: 99%